Efficiency of the European Union Banking Sector: A Panel Data Approach - Ferreira, Candida (International Journal of Business Management and Finance Research, 2025)
This paper aims to analyse the evolution of efficiency within a substantial panel of 784 pertinent banks operating across all 27 European Union (EU) member states, covering the period from 2006 to 2021. It further aspires to furnish actionable recommendations for bank managers and policymakers aimed at enhancing the performance and resilience of the EU banking sector. The study employs Data Envelopment Analysis (DEA) techniques, which encompass various concepts and measures of bank efficiency, along with the results provided by the Malmquist index. Banks are assumed to produce three outputs: loans, other earning assets, and non-earning assets, which are generated using three inputs: interest expenses, non-interest expenses, and equity The principal findings reveal the existence of inefficiencies predominantly stemming from suboptimal combinations of inputs and outputs as opposed to scale inefficiencies. The computed values of the Malmquist index exhibit a general trend of progress in efficiency, with notable exceptions observed during the global financial crisis and, to a lesser extent, during the period from 2015 to 2017. The insights gleaned from this study indicate that EU bank managers possess the potential to improve efficiency through more judicious combinations of inputs and cost management strategies. The significance of the banking crisis is reaffirmed as a critical determinant. Furthermore, the paper underscores the pivotal role of policymakers, particularly during the years of 2015 to 2017, which witnessed significant developments within the European Banking Union framework. This research does not substantiate the assertion that banks from any particular EU country maintain a consistent position of superior efficiency, as the rankings exhibit variability depending on the diverse constructs and metrics utilized to gauge bank efficiency. Nonetheless, it is feasible to identify certain countries, such as Finland and the Netherlands, that are consistently positioned among the highest tiers in the various efficiency ranking lists.